An Innovative Blended Preclinical Curriculum in Clinical Epidemiology and Biostatistics: Impact on Student Satisfaction and Performance. (May 2016) - Evans, Kambria H.; Thompson, Atalie C.; O'Brien, Colin; Bryant, Madika; Basaviah, Preetha; Prober, Charles; Popat, Rita A.
Abstract : Problem: There is little understanding of the impact of teaching clinical epidemiology and biostatistics in a flipped or blended format. At Stanford University School of Medicine, the quantitative medicine (QM) curriculum for first-year students was redesigned to use a blended format, in response to student feedback. Approach: The blended QM curriculum introduced in 2013 integrated self-paced, online learning with small-group collaborative learning. The authors analyzed the blended format's impact on student satisfaction and performance, comparing the pilot cohort of students (n = 101) with students who took the traditional curriculum in 2011 and 2012 (n = 178). They also analyzed QM resource utilization in 2013. Outcomes: The blended curriculum had a positive impact on satisfaction and mastery of core material. Comparing the 2013 blended cohort with the 2011–2012 traditional cohort, there were significant improvements in student satisfaction ratings (overall, P < .0001; organization, P < .0001; logical sequence, P = .008; value of content, P < .0001). The mean (SD) overall satisfaction rating for small-group sessions increased: 3.40 (1.03) in 2013 versus 2.79 (1.00) in 2011 and 2.83 (1.06) in 2012. Performance on the QM final exam showed no significant changes in 2013 versus 2011 and 2012. The majority of students in 2013 reported using the QM online videos as their primary learning resource (69%–85% across modules). Next Steps: The positive impact of the curricular elements studied will inform continued development of the QM curriculum. Features of the curriculum could serve as a model for future blended courses.